2022
DOI: 10.7759/cureus.22900
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With COVID-19 Symptoms and Potential Vertical Transmission During Pregnancy: A Retrospective Cohort Study

Abstract: Objective The COVID-19 pandemic is of special concern for pregnant women. A growing body of evidence suggests the virus can have a deleterious impact upon outcomes related to birth and newborn health. There is a paucity of published research demonstrating the factors that influence disease severity among those who are pregnant, while a growing body of evidence demonstrates that vertical transmission occurs. Our study investigated the impact of maternal characteristics upon COVID-19 outcomes, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[ 33 ] Obesity leads to more adipose tissue and more angiotensin- converting enzyme 2 (ACE2) receptors on the cell surface, in which SARS-CoV-2 binds and penetrates in the cell [ 34 ]. Prior studies have also found a positive correlation among prenatal BMI and COVID-19 infection [ 35 ]. Likewise, diabetes involves a chronic inflammatory effect together with a prothrombotic stage that might play a worsen response to infections [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 88%
“…[ 33 ] Obesity leads to more adipose tissue and more angiotensin- converting enzyme 2 (ACE2) receptors on the cell surface, in which SARS-CoV-2 binds and penetrates in the cell [ 34 ]. Prior studies have also found a positive correlation among prenatal BMI and COVID-19 infection [ 35 ]. Likewise, diabetes involves a chronic inflammatory effect together with a prothrombotic stage that might play a worsen response to infections [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 88%
“…No positive results for vertical transmission were observed. Previous studies have described positive rates of 2 to 4.4 percent of neonatal COVID-19 PCR tests at delivery ( 29 , 49–51 ), but vary widely, PCR tests of COVID-19 such as amniotic fluid, cord blood, placenta, and breast milk have found no evidence of vertical transmission ( 52–54 ), and further research is needed.…”
Section: Discussionmentioning
confidence: 98%
“…Further data are needed to better understand how body weight and nutrition can influence the prognosis of COVID-19 in pregnancy, and how pre-pregnancy normalization of BMI and tailored nutritional supplementation can affect pregnancy outcomes [ 24 , 26 , 34 , 35 , 36 , 37 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%